Effects of ambient glycaemic state on growth hormone responsiveness in insulin-dependent diabetes - Ismail, I.S.; Scanlon, M.F.; Peters, J.R. (Wiley, 1991)
We wished to examine the effects of ambient glycaemia on hypothalamic somatostatinergic tone in insulin-dependent diabetes mellitus. After 6-hour periods of either euglycaemia (5 mmol/l) or hyperglycaemia (15 mmol/l), exercise-induced GH secretion was measured. Seven insulin dependent diabetics with no evidence of complications were recruited. There was no significant difference between basal GH levels during euglycaemia and hyperglycaemia (5.50 vs 5.53 mU/l). Nor was there a significant difference when mean \ GH levels (33.9 vs 27.4 mU/l) or mean area under GH curve (2331 vs 4038 mU min/l) during euglycaemia or hyperglycaemia were compared. We find no evidence therefore to support short-term effects of ambient glucose concentration on GH responsiveness, and by inference no direct effect of shortterm changes in glycaemic control on hypothalamic release of somatostatin in the aetiology of GH hypersecretion in insulin-dependent diabetes mellitus.